2013
DOI: 10.1002/chem.201203158
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Level Alloying and De‐alloying in Doped Gold Nanoparticles

Abstract: Atomically precise alloying and de-alloying processes for the formation of Ag-Au and Cu-Au nanoparticles of 25-metal-atom composition (referred to as Ag(x)Au(25-x)(SR)18 and Cu(x)Au(25-x)(SR)18 , in which R = CH2CH2Ph) are reported. The identities of the particles were determined by matrix-assisted laser desorption ionization mass spectroscopy (MALDI-MS). Their structures were probed by fragmentation analysis in MALDI-MS and comparison with the icosahedral structure of the homogold Au25(SR)18 nanoparticles (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 40 publications
(110 reference statements)
4
89
0
1
Order By: Relevance
“…87 Note that Jin et al also reported these Cu-doped clusters to be unstable. 88 The atomic radius of Cu (1.28 ¡) is smaller than that of Ag (1.44 ¡). Cu doping therefore distorts the framework structure significantly, 87 which likely destabilizes Au 25¹n Cu n (SR) 18 ; thus, only up to five Cu atoms can be incorporated into Au 25 -(SR) 18 .…”
Section: Chemical Compositionmentioning
confidence: 97%
“…87 Note that Jin et al also reported these Cu-doped clusters to be unstable. 88 The atomic radius of Cu (1.28 ¡) is smaller than that of Ag (1.44 ¡). Cu doping therefore distorts the framework structure significantly, 87 which likely destabilizes Au 25¹n Cu n (SR) 18 ; thus, only up to five Cu atoms can be incorporated into Au 25 -(SR) 18 .…”
Section: Chemical Compositionmentioning
confidence: 97%
“…Refs. 21,23,28 . Indeed, during the revision stage of the present perspective article, a further review has appeared on-line 70 .…”
Section: Monolayer-protected Clustersmentioning
confidence: 98%
“…Section 2 is then dedicated to a brief survey of this topic. Moreover, a sub-field evolving in a particularly tumultuous fashion among alloy nanosystems is that of monolayer-protected, size-selected clusters [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . For clarity of presentation, we then single out these latter systems apart, so that in Section 3 we discuss other nanosystems, i.e., nanoclusters and nanorods or nanowires both free and in a less interacting environment, while Section 4 will be devoted to monolayer-protected alloy clusters, also providing a literature review of the explosive growth in this sub-field.…”
Section: Introductionmentioning
confidence: 99%
“…270 The Pt atom occupies position at the core centre, similarly to PdAu 24 (SR) 18 Unlike platinum and palladium, which form singly doped systems MAu n L m , silver and copper can form bimetallic variable-composition clusters. In particular, the Ag x Au 257x (SC 12 H 25 ) 18 (x = 1 ± 11), 272 Ag x Au 257x (SCH 2 Bn) 18 (x = 1 ± 8), 273 Ag x Au 257x (SCH 2 Bn) 18 (x = 6.7), 103 Ag x Au 387x (SR) 24 (x =1, 3, 5, 6), 100 and Ag x Au 1447x (SCH 2 Bn) 60 (x = 30, 34, 52, 53, 60) 99 clusters were synthesized. They are multiply doped analogues to the Au 25 (SR) 18 , Au 38 (SR) 24 and Au 144 (SR) 60 clusters considered above.…”
Section: Gold Clusters Stabilized By Phosphine Ligandsmentioning
confidence: 99%
“…For instance, the maximum number of silver atoms (x max ) is 60 for Ag x Au 1447x (SCH 2 Bn) 60 clusters 99 and only 8 for Ag x Au 257x (SCH 2 Bn) 18 . 273 Reactions of gold nanoparticles with AgSCH 2 Bn result in the [Ag x Au 257x (PPh 3 ) 10 (SCH 2 Bn) 5 Cl 2 ] 2+ clusters containing at most twelve silver atoms. 274 The thirteenth silver atom can be introduced into the cluster by the reaction of Au 11 with AgSCH 2 Bn.…”
Section: Gold Clusters Stabilized By Phosphine Ligandsmentioning
confidence: 99%